Pemanfaatan Loose Parts Untuk Meningkatkan Kemampuan Berpikir Simbolik Dan Motorik Halus Anak PAUD Tiara Madani Caruban. - Narwati, Lilik Yuni; Sucipto; Silver, Soesiana Tri Eka (Universitas Islam Lamongan, 2024)
The use of media in learning is an important part of providing stimulation to early childhood students in order to improve their abilities. The ability that is not limited to cognitive aspects but also other aspects to lead children to enter the next basic education. The aim of this study was to determine the effect of using loose parts media on increasing children's symbolic thinking skills and fine motor skills. This study is a quasi-experiment using a single group design with pretest and posttest. The ability indicators used are based on Permendikbud No. 137/2014. The research population also as sample was 20 students 5-6 years old in PAUD Tiara Madani, Academic Period: 2022-2023. Data analysis used paired sample t-test and N-gain. The results of the hypothesis test for the treatment effect on symbolic thinking skills obtained p value= 0.00 (<0.05) and N-gain= 0.6354 (moderate category) and the treatment effect on fine motor skills obtained p value= 0.00 (<0.05) and N-gain= 0.6233 (moderate category). From this study it can be concluded that the use of Loose Parts media has a significant effect on students' symbolic thinking skills and fine motor skills.